PENERAPAN PEMBELAJARAN EXPERIENTIAL LEARNING UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN IPA KELAS V SEKOLAH DASAR - Aprilia, Septi (Premiere Educandum, 2015)
This research aims to improve the outcomes of student learning and teacher skills in learning science by implementing the experiential learning model. This research is an action class research which is done in two cycles. The subjects of this research are teacher and students in fifth grade on Bulukantil Elementary School of Surakarta academic year 2014/1015. Data collection techniques used the methods of test and observation. Based on the results of the research shown increasing in the average of studied results from cycle I to cycle II from 61, 07 with percentage of 60,7 % to 75,09 with percentage rose to 85%. The research also shown increase in the skills of teachers, on average cycle I teacher skills was 3, 11 with percentage of 48.3% (good in scale) in cycle II rose to 3,5 with percentage88.8% (very good in scale). As a result the experiential learning model can improve the quality of learning that can be suggested to apply in learning especially in natural science.Keyword: experiential learning model, Study result, teacher skills